Influence of Orthodontic Dental Movement on the Healing Process of Teeth With Periapical Lesions - Souza, Ricardo Sampaio de [UNESP]; Gandini, Luiz Gonzaga [UNESP]; Souza, Valdir de [UNESP]; Holland, Roberto [UNESP]; Dezan Junior, Eloi [UNESP] (Elsevier B.V., 2006)
The purpose of this study was to histomorphologically evaluate (in dog's teeth) the influence of tooth movement in the healing of chronic periapical lesions. Thirty roots of incisors and premolars of two dogs (1-year-old) were used in this research. After pulpectomy, the root canals remained exposed to the oral environment for 6 months for achievement of periapical lesions. Twenty root canals were biomechanically prepared and received a calcium hydroxide dressing for 14 days before being filled with gutta-percha points and Sealapex sealer. After root canal treatment, some incisors were submitted to orthodontic movement, whereas the other roots remained without orthodontic movement. The orthodontic appliance was removed at 5 months and 15 days after treatment, the dogs were killed 15 days later and the specimens were prepared for histomorphological analysis. The results showed that the orthodontic movement delayed, but did not hinder, the periapical healing process. (J Endod 2006;32:115-119)